2011
DOI: 10.1007/978-3-642-25513-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Group Signature with Constant Revocation Costs for Signers and Verifiers

Abstract: Abstract. Membership revocation, being an important property for applications of group signatures, represents a bottleneck in today's schemes. Most revocation methods require linear amount of work to be performed by unrevoked signers or verifiers, who usually have to obtain fresh update information (sometimes of linear size) published by the group manager. We overcome these disadvantages by proposing a novel group signature scheme, where computation costs for unrevoked signers and potential verifiers remain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…3) Though signing/verification costs are constant, the size of gpk is O( √ N ) [22] or the size of RL is O(N ) [23]. 4) All costs are asymptotically quite efficient (less than O(log N )), but the real costs are inefficient [24], [19], [25].…”
Section: ) Though the Verification Cost Is O(r) The Signing Costmentioning
confidence: 99%
“…3) Though signing/verification costs are constant, the size of gpk is O( √ N ) [22] or the size of RL is O(N ) [23]. 4) All costs are asymptotically quite efficient (less than O(log N )), but the real costs are inefficient [24], [19], [25].…”
Section: ) Though the Verification Cost Is O(r) The Signing Costmentioning
confidence: 99%
“…The reason is that, in known pairing-based accumulators [53,27], public keys have linear size in the maximal number of accumulated values (unless one sacrifices the constant size of proofs of non-membership as in [5]), which would result in linear-size group public keys in straightforward implementations. Recently [35], Fan et al suggested a different way to use the accumulator of [27] and announced constant-size group public keys but their scheme still requires the group manager to publicize O(N ) values at each revocation. In a revocation mechanism along the lines of [29], Boneh, Boyen and Shacham [16] managed to avoid linear dependencies.…”
Section: Our Contributionmentioning
confidence: 99%
“…Since Chaum and Van Heyst introduced the group signature concept in [98], researchers have proposed a large number of group signature schemes [99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118].…”
Section: The State-of-the-art Group Signature Schemesmentioning
confidence: 99%
“…The security of the design relies on the strong Diffie-Hellman and the Decision Linear assumptions. Since then, various other group signatures built on bilinear maps have been proposed in [106,115,109,119,116,117,118,110,113,114]. Particularly, schemes [109,119] are designed to provide backward unlinkability for revoked users, i.e., even a member is revoked, signatures generated by this member before the revocation remain anonymous.…”
Section: The State-of-the-art Group Signature Schemesmentioning
confidence: 99%
See 1 more Smart Citation